Plate ice maker problems: solutions, analysis, redesign and rebuild - Atwan, Nabeel (جامعة بوليتكنك فلسطين - ميكانيك, 2010)
The purpose of the project is to detect the prolems of ice maker that was build befor, by doing recaluculation and redesign and rebuild to the ice maker system by using components of the refrigeration cycle, compressor, condenser, expansion valve and evaporator, to produce a plate of ice. The refrigerant R134a was selected as suitable working fluid. This system consists of one cycle , where the cucle operates between( -21 and 35 C). Theoretical design and building of the system will be made, according to the calculations that will be shown in the next chapters. This unit will be used in the university laborites to show the process of forming ice.
CD , no of pages 80 , 25735, ميكانيك 19/2010 , in the store
Keywords: Machines - problems